Lameness Localization in Dogs: An Exploratory Study of the Translation of the Equine Flexion Test to Canine Orthopaedics - Grosjean, Diane; De Bakker, Evelien; Mugnier, Amélie; Verschooten, Francis; Rytz, Ulrich; Forterre, Franck; Samoy, Yves; Van Ryssen, Bernadette (VCOT Open, 2022)
Objectives The aim of this study was to describe the method and feasibility of the flexion test (FT) as a diagnostic tool to localize lameness on dogs.Study Design Canine FT was designed and based on the FT routinely used on horses. In dogs, the test consisted in a flexion of a joint to its full range of motion for 1 minute. Eventual increased lameness was then evaluated. The gait was evaluated using a visual analogue scale. An increase in the lameness score compared with the baseline score was considered as a positive result.The method was described for every major joint of the appendicular skeleton and was evaluated in sound and lame dogs. To evaluate the feasibility, the FT was applied for 3 minutes in eight healthy dogs on all joints. On 27 clinically lame dogs, flexion was applied for 1 minute on the joints with a suspected pathology and on their contralateral side used as a control.Results The FT was feasible and well tolerated by the sound dogs on all joints and no positive results were recorded. On clinically lame dogs, lameness increased in 81.5% of dogs. These cases were afterwards diagnosed with an orthopaedic-related disorder and then defined as true positives. False negative results occurred in 18.5% of the lameness cases.Conclusion The FT is safe and easy to perform. It did not produce any false positive results. False negatives might occur in a minor number of cases, implying that a negative result does not exclude a joint pathology.
Keywords: lameness evaluation; orthopaedic examination; joint pain; diagnostic tool; locomotor system